Novel metal-doped bacteriostatic hybrid clay composites for point-of-use disinfection of water. Issue 3 (June 2017) - Unuabonah, Emmanuel I.; Kolawole, Matthew O.; Agunbiade, Foluso O.; Omorogie, Martins O.; Koko, Daniel T.; Ugwuja, Chidinma G.; Ugege, Leonard E.; Oyejide, Nicholas E.; Günter, Christina; Taubert, Andreas
Graphical abstract: Highlights: Development of a new class of composites from agrogenic waste and clay. Hybrid clay kept bacteria level of 10 3  cfu/mL at zero for up to 24 h. Strong correlation between the amount of Zn and the activity of composite. Bacteriostatic mechanism of removal of enteric bacteria from water. Abstract: This study reports the facile microwave-assisted thermal preparation of novel metal-doped hybrid clay composite adsorbents consisting of Kaolinite clay, Carica papaya seeds and/or plantain peels ( Musa paradisiaca ) and ZnCl2 . Fourier Transformed IR spectroscopy, X-ray diffraction, Scanning Electron Microscopy and Brunauer–Emmett–Teller (BET) analysis are employed to characterize these composite adsorbents. The physicochemical analysis of these composites suggests that they act as bacteriostatic rather than bacteriacidal agents. This bacterostactic action is induced by the ZnO phase in the composites whose amount correlates with the efficacy of the composite. The composite prepared with papaya seeds (PS-HYCA) provides the best disinfection efficacy (when compared with composite prepared with Musa paradisiaca peels-PP-HYCA) against gram-negative enteric bacteria with a breakthrough time of 400 and 700 min for the removal of 1.5 × 10 6  cfu/mL S. typhi and V. cholerae from water respectively. At 10 3  cfu/mL of each bacterium in solution, 2 g of both composite adsorbents kept the levels the bacteria in effluent solutions at zero for up to 24 h. Steam regeneration of 2 g of bacteria-loaded Carica papaya prepared composite adsorbent shows a loss of ca. 31% of its capacity even after the 3rd regeneration cycle of 25 h of service time. The composite adsorbent prepared with Carica papaya seeds will be useful for developing simple point-of-use water treatment systems for water disinfection application. This composite adsorbent is comparatively of good performance and shows relatively long hydraulic contact times and is expected to minimize energy intensive traditional treatment processes.